An Analysis of Guided Peer Review to Improve Writing Skill on Personal Recount Texts for High School Students in Bojonegoro - Mohammad Fatoni; Ahmad Tauchid (Jurnal Pendidikan Edutama, 2020)
Abstract: This research aims to analyze guided peer review to improve writing skill on personal recount texts for high school students in Bojonegoro in the aspects of (1) How is the process of implementing guided peer review (2) the students’ problems in writing personal recount texts (3) how the students’ writing after using guided peer review. This research uses colaborative classroom action research method. Analysis of the students’ problems in composing personal recount texts is analyzed in five components of writing such as content, organization, vocabulary, languge use, and mechanics. The Results of the analysis of average scores reveal that the students have problems in all components of writing in composing personal recount text in the initial drafts of the first cycle. However, there is significant improvement on the students class mastery of final draft from the first to second cycles. They are 53% and 83% students reach the minimum score criteria. Operational comments and suggestions help their peer to develop their writing better. It means guided peer review is able to improve the students writing skill in pesonal recount texts. Keyword: Guided peer review, personal recount texts, writing components Abstrak: Penelitian ini bertujuan untuk menganalisis guided peer review untuk meningkatkan keterampilan menulis teks personal recount pada peserta didik SMA di Kabupaten Bojonegoro dalam hal (1) Bagaimana proses implementasi guided peer review (2) permasalahan peserta didik dalam menulis teks personal recount dan (3) bagaimana tulisan peserta didik setelah menggunakan guided peer review. Penelitian ini menggunakan metode penelitian tindakan kelas kolaboratif. Analisa permasalahan penulisan teks personal recount pada semua komponen keterampilan menulis antara lain isi, organisasi, kosa kata, grammar, dan mekanik.  Hasil analisis dari nilai rata-rata mengungkapkan bahwa peserta didik memiliki masalah dalam semua komponen keterampilan menulis pada draf awal di siklus pertama. Namun, ada peningkatan yang signifikan pada penguasaan kemampuan menulis pada draf akhir dari siklus pertama hingga kedua sebesar 53% dan 83% peserta didik dapat mencapai nilai kriteria ketuntasan minimal (KKM). Komentar dan masukkan yang jelas membantu teman sebayanya dalam mengembangkan tulisannya lebih baik. Ini berarti guided peer review dapat meningkatkan kemampuan menulis teks personal recount peserta didik. Kata kunci: peer review terbimbing, teks personal recount, komponen tulisan.